2021
DOI: 10.1371/journal.pcbi.1008231
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic bistable switches enhance robustness and accuracy of cell cycle transitions

Abstract: Bistability is a common mechanism to ensure robust and irreversible cell cycle transitions. Whenever biological parameters or external conditions change such that a threshold is crossed, the system abruptly switches between different cell cycle states. Experimental studies have uncovered mechanisms that can make the shape of the bistable response curve change dynamically in time. Here, we show how such a dynamically changing bistable switch can provide a cell with better control over the timing of cell cycle t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 103 publications
0
29
0
Order By: Relevance
“…Interestingly, the bistable nature of the cell cycle transitions itself can provide the means for this regulation by shifting the (in)activation thresholds (i.e. folding points) of the S-shaped response curves to lower or higher levels [ 13 , 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the bistable nature of the cell cycle transitions itself can provide the means for this regulation by shifting the (in)activation thresholds (i.e. folding points) of the S-shaped response curves to lower or higher levels [ 13 , 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistic studies of miR-200-regulated networks have revealed the role of these miRNAs as central hubs of two-node double negative feedback loops (DNFL) in which transcription factors (TF) suppress expression of miR-200 which, in turn, negatively regulate the TF ( Figure 2 ). Interestingly, DNFL generate bi-stable switches that confer robustness and plasticity to critical regulatory circuits which, in response to variation of biological parameters beyond a threshold value, abruptly switch between on- and off-states [ 242 ]. Collected evidence converges over a central position of the miR-200 family in at least 4 DNFL ( Figure 2 ) controlling the EMT-MET switch (ZEB/SNAIL), as well as two pervasive shapers of the cell’s transcriptomic landscape (Myc and SIRT1), which play a key role in the progression towards metastatic dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our results could be expanded by including nuclei in our extract preparations, which could be achieved by supplying demembranated sperm chromatin into Xenopus extracts. Theoretical work suggested that the extra dynamic bistable switch induced by nuclear translocation promotes the robustness of cell-cycle oscillations to noise ( 59 ). How changes in cytoplasmic density affect a system in which nuclei are present is currently unknown and can be a promising avenue for research.…”
Section: Discussionmentioning
confidence: 99%